ORGANOLEPTIK DAGING DADA ITIK MAGELANG DENGAN PERBEDAAN LAMA PERENDAMAN SARI BELIMBING WULUH (Averrhoa bilimbi L.) - Hidayah, Nur; Pramono, Pradipta B; Nur, Hidayah (Universitas Djuanda, 2022)
This study aims to utilize of bilimbi fruit and know the length of soaking of the best bilimbi fruit in the organoleptic test properties of the chest of Magelang duck. The experimental design used in this study is a Complete Randomized Design with 4 treatments of differences in the length of soaking bilimbi fruit (0, 20, 40, 60 Minutes) and 5 replays with a concentration of 40%. The observation data was analyzed with ANOVA at a real level of 5%, then if there is different data between treatments, Duncan Multiple Range Test is conducted. The results showed that the difference in the duration of soaking bilimbi fruit juice for 20-60 minutes in Magelang duck breast meat had a significant effect on the change in the color of the meat from red (4.25) to slightly gray (2.54-3.11). The aroma changed from slightly fishy (3.11-3.35) at 0-20 minutes of soaking bilimbi fruit and close to not fishy (3.64-3.65) at 40-60 minutes of immersion. However, the difference in soaking time up to 60 minutes did not affect the taste (2.54-2.90 somewhat addic), texture (2.79-3.13 yaitu not tender near tender), and favorite (2.58-2.93 is a bit like). The duration of soaking starfruit in Magelang duck breast meat for up to 60 minutes was able to reduce the fishy aroma and change color, but did not affect the taste, texture, and preference